Antioxidant for Neurological Diseases and Neurotrauma and Bioengineering Approaches - Nasera Rizwana; Vipul Agarwal; Manasa Nune (MDPI AG, 2021)
Antioxidants are a class of molecules with an innate affinity to neutralize reactive oxygen species (ROS), which are known to cause oxidative stress. Oxidative stress has been associated with a wide range of diseases mediated by physiological damage to the cells. ROS play both beneficial and detrimental roles in human physiology depending on their overall concentration. ROS are an inevitable byproduct of the normal functioning of cells, which are produced as a result of the mitochondrial respiration process. Since the establishment of the detrimental effect of oxidative stress in neurological disorders and neurotrauma, there has been growing interest in exploring antioxidants to rescue remaining or surviving cells and reverse the neurological damage. In this review, we present the survey of different antioxidants studied in neurological applications including neurotrauma. We also delve into bioengineering approaches developed to deliver antioxidants to improve their cellular uptake in neurological applications.